Characterization of the HIV-1 Subtypes present in Córdoba (Argentina) from nearly the beginning of the infection, using the Pol and Env genes - González Ittig, Raúl Enrique (2017)
Objective: Identify the HIV-1 subtypes circulating in Córdoba, Argentina, in the period 1986-2001. Methods: Sequences of the pol and env genes from strains of Córdoba were compared with those of the HIV-1 M-group (several subtypes and circulating recombinant forms). Then, to determine if Cordobas subtypes had a single or multiple geographic origins, sequences were subdivided into pure-subtype data sets (avoiding the effects of recombination) and compared with sequences of diverse geographic origin. Results: Eighteen strains were subtype B, seven B/F1, one C and one F1. The B/F1 were: two CRF12_B/F1 and five unique recombinant forms (URF_B/F1). Córdoba?s subtype B would have multiple geographic origins, while subtypes F1 and C would have been introduced from Brazil or from Buenos Aires. Conclusions: The HIV-1 infection in Córdoba was complex since its very beginning and reveals its close contact, through tourism and commercial activities, with Buenos Aires and Brazil.